الطب النبوي: دراسة في ضوء التصرفات النبوية (Prophetic Medicine: A Studies in Tasarrufat Nabawiyyah Contexts) - Mahmad Robbi, Ahmad Akram; Awang Hamat, Mohd Afandi (Journal of Hadith, Universiti Sains Islam Malaysia, 2018)
The Medical Prophetic has a large area in Sharia. The Islamic Sharia has focused on the body treatment, also the heart treatment because both of them are considered as a one of ways to conform the Maqasid Sharia in Islam. They are including in needs, without them, the purpose of Sharia is cannot be achieved. Therefore, Sharia is acquiring that the body and heart treatment are one of the biggest Sharia purposes. The Islamic scholars are always arguing each other in their way of interaction with the Prophetic Tradition in Medical Issues. There is who claims that the Prophetic Tradition in Medical Issues is one of the Sharia obligations, and there is no space to offence such as Solah, Zakat, Saum and Hajj. And there are who claims that the Prophetic Tradition in Medical Issues isn’t part of Sharia, it is included in custom and need some experiments made by pros. The Islamic scholars are agreeing that the area of study in Prophetic Medical issues in Tibb Qulub is part of ghaibiyat, there are no space for them for looking forward in this study. But, in Tibb al-Badn, this is the field that they are arguing to. This study applies some methodology such as analytical and comparative studies. This study collects some information from jurist’s opinions that related to the study and comparing them to find the strongest one. This study has a relationship with the field of Maqasid Sharia indirectly because Prophetic Medical is assumed as one of ways to confirm the Sharia purposes (to claim the public interest and neglect the evil). Interaction with the Prophetic Tradition in Medical Issues with a good understanding drives to achieve the true of Sharia Purpose.